Decalcifying effects of antimicrobial irrigating solutions on root canal dentin - Ferrer-Luque, Carmen M. (Medicina Oral S.L., 2013)
Objective: The aim of this study was to determine the decalcifying efficacy of 7% maleic acid (MA), 2% chlorhexidine (CHX), and combinations of 7% MA + 0.2% cetrimide (CTR) and 2% CHX + 0.2% CTR, in four time periods. Study Design: Four specimens per tooth were obtained from a 2-mm thick slice of the cervical third of the root of ten human incisors. At 1, 2, 3 and 5 minutes of immersion, the concentrations of Ca2+ were measured by atomic absorption spectrophotometry. The results were analyzed using the Mann-Whitney U-test. Results: Statistically significant differences were seen for the extracted calcium in all time periods. The amount of calcium extracted by 7% MA was the highest at all four immersion times, followed by 7% MA + 0.2% CTR. Two percent CHX and its combination with 0.2% CTR extracted virtually no calcium. Conclusions: The decalcifying capacity of 7% MA and 2% CHX diminished when combined with 0.2% CTR. Key words:Cetrimide; chlorhexidine; decalcification; maleic acid; spectrometry.